Respiratory manifestations of ANCA‐associated vasculitis. (12th May 2016) - Greenan, Kerry; Vassallo, Diana; Chinnadurai, Rajkumar; Ritchie, James; Shepherd, Kate; Green, Darren; Ponnusamy, Arvind; Sinha, Smeeta
Abstract: Background: The prevalence of pulmonary manifestations of ANCA‐associated vasculitis (AAV) is not well understood. This study describes the prevalence of respiratory complications of AAV detected via imaging in patients presenting to a secondary renal centre and describes the associations with mortality. Methods: 105 patients with AAV were identified from the Chronic Renal Insufficiency Standards Implementation Study (CRISIS). CRISIS is a prospective epidemiological study of patients with chronic kidney disease stages 3–5, both who did and did not require dialysis on presentation. Patients were recruited between 2000 and 2013. Results: A chest X‐ray was performed in 81.0% of patients with AAV on presentation, of which 56.5% were abnormal. A computed tomography (CT) thorax was performed in 27 patients during the course of their disease: 92.6% showed abnormalities, most commonly fibrosis (63.0%) and bronchiectasis (44.4%). Pulmonary vascultitis was confirmed in 22 of 105 patients (21.0%) after respiratory review or demonstrated by associated changes associated on CT scan. In a Cox regression model, there was no significant association between pulmonary vasculitis and mortality ( P  = 0.088), although there was a trend towards increased mortality with pulmonary vasculitis. Conclusions: Pulmonary manifestations of AAV were common, however only a small proportion of patients had had thorough respiratory investigations, suggesting that the pulmonary manifestations of AAV may be under‐diagnosed.